Selection of inventory accounting methods for industrial and consumer goods sectors: the relationship between inventory variability - Arinal Muna; Aoliyah Firasati; Wilda Fuji Lestari (RTTM, 2023)
Inventory has a significant impact on the success of a company’s operational procedures. Each company can select a method of distribution that is appropriate for its needs, and in selecting a method of distribution, the company can learn (opportunity) about the method of distribution that will be used in the company. Opportunity measure is an action taken by management in determining the inventory method that maximizes satisfaction and is profitable for the company. As a result, selecting a reliable method of gaining access to information is critical, because failing to do so will have a negative impact on your financial situation. The goal of this research is to eliminate any negative effects on the variability of the business, the size of the company, and the level of risk associated with the selection of a business assurance method. Purposive sampling was used to choose the manufacturing firm that would serve as the sample for this investigation. This company is part of the consumer products industrial sector and is listed on the Indonesia Stock Exchange. There are 40 businesses that meet the criteria, with 36 businesses using the average method and 4 businesses using the FIFO method. Data collection the technique employing second-level data. The data analysis technique used is logistic regression analysis. The results of the hypothesis testing show that the variability of inventory is affected by the choice of a inventory accounting method, but the size of the company and the level of risk are not